Lotka’s Law and the Literature of Library and Information Science in Turkey - Murat Yılmaz (Türk Kütüphaneciliği)
The aim of the study is to test the applicability of Lotka’s Law for the literature of library and information science in Turkey. The database of the study is 1399 papers published in The Bibliography of Articles in Turkish Periodicals between 1952 and 2000, by 604 researchers in the field of library and information science. The results of the study present the distribution of productivity of Lotka’s inverse square law does not fit the distribution of the data constituted by the researchers in the field of library and information science in Turkey. In other words it was determined that Lotka’s inverse square law does not apply the literature of library and information science in Turkey. Furthermore it was determined that Lotka’s inverse power law fits the value of n (2,1128) calculated for the literature of library and information science in Turkey.